Utilization Of The Merdeka Teaching Application With Belajar.Id Account - Muhammad Iqbal; Adi Mas Afandi (STMIK Royal, 2022)
Abstract: SMP Negeri 7 Kisaran is a school with a driving status focused on developing student learning outcomes holistically. Although the COVID-19 pandemic is not over, learning activities must still be carried out. The Ministry of Education and Culture issued a breakthrough learning innovation that became its own attraction during the pandemic, namely the belajar.id account that allows one learning account that can access various digital learning flatforms. One of the flatforms supported by belajar.id on this devotion is the Merdeka Mengajar Application. The purpose of this PKM activity is about the use of flatform belajar.id so that it can be optimized as it should be. The result of this devotion gets some shortcomings in the independent teaching application, starting from the class can not be removed and assessments are only obtained from the ministry of education and culture, so that the expectations of teachers in the latest version of some of these features are available and other assessments can vary. Keywords: account; belajar.id; learning; kemendikbud; media. Abstrak: SMP Negeri 7 Kisaran merupakan sekolah dengan status penggerak berfokus pada pengembangan hasil belajar siswa secara holistik. Meski pandemi COVID-19 belum berakhir, Kegiatan pembelajaran harus tetap dilakukan. Kemdikbud mengeluarkan terobosan inovasi belajar yang menjadi daya tarik sendiri disaat pandemi yaitu akun belajar.id yang mengizinkan satu akun pembelajaran yang dapat mengakses berbagai flatform pembelajaran digital. Salah satu flatform yang didukung oleh belajar.id pada pengabdian ini yaitu Aplikasi Merdeka Mengajar. Tujuan dari kegiatan PKM ini tentang pemanfaatan flatform belajar.id agar dapat dioptimalkan sebagaimana mestinya. Hasil dari pengabdian ini mendapatkan beberapa kekurangan pada aplikasi merdeka mengajar, dimulai dari kelas tidak dapat dihapus dan assesmen hanya diperoleh dari kemdikbud, sehingga harapan guru pada versi terbaru beberapa fitur tersebut tersedia dan assesmen lainnya dapat bervariasi.Kata kunci: akun; belajar.id; media; kemendikbud; pembelajaran